2015
DOI: 10.1093/brain/awv107
|View full text |Cite
|
Sign up to set email alerts
|

The role of tau in the pathological process and clinical expression of Huntington’s disease

Abstract: Tau has recently been implicated in Huntington’s disease, but the nature of its involvement is unclear. Vuono et al. reveal tau oligomers and hyperphosphorylated tau aggregates in post-mortem Huntington’s disease brains, including those from young-onset cases. Genotype-phenotype analysis of a large patient cohort shows that tau haplotypes influence cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 41 publications
8
138
3
Order By: Relevance
“…We have previously demonstrated that tau oligomers also act as the pathological species in the disease progression of progressive supranuclear palsy (PSP) patients 40. Moreover, tau oligomers have been identified in cortical and striatal brain regions in patients with other amyloid diseases, such as Huntington's disease 41. These observations further support testing the levels of tau oligomers in the CSF of other tauopathies as well as other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 63%
“…We have previously demonstrated that tau oligomers also act as the pathological species in the disease progression of progressive supranuclear palsy (PSP) patients 40. Moreover, tau oligomers have been identified in cortical and striatal brain regions in patients with other amyloid diseases, such as Huntington's disease 41. These observations further support testing the levels of tau oligomers in the CSF of other tauopathies as well as other neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 63%
“…Other brain areas are also affected but less severely. In line with this, two splicing alterations have been described that may be important for the pathogenesis of HD; one in the HTT gene itself giving rise to a highly toxic N-terminal form of mutant HTT (27) and more recently, we and others have demonstrated missplicing of the MAP Tau exon 10 in HD patients (7,31). HD thus belongs to the group of CAG trinucleotide repeat/PolyQ disorders (22).…”
Section: Introductionmentioning
confidence: 65%
“…Further, PD-causing mutations in α-Syn increase its nuclear accumulation (Fares et al, 2014; Kontopoulos et al, 2006). Moreover, postmortem studies of tissue from AD and Huntington disease patients indicate that misfolded tau accumulates in the nucleus of neurons in the form of rod-like deposits (Fernández-Nogales et al, 2014; Vuono et al, 2015). Our finding that TRIM28 drives the nuclear accumulation of α-Syn and tau provides new mechanistic insight into the steps that lead to the pathogenicity of these proteins and highlights a shared pathway for therapeutic targeting.…”
Section: Discussionmentioning
confidence: 99%